2017
DOI: 10.5604/12321966.1230674
|View full text |Cite
|
Sign up to set email alerts
|

Variations in physical activity of male and female students from the Ukraine in health-promoting life style

Abstract: Introduction. A large-scale research was performed concerning issues relating to physical activity as an important factor in a healthy lifestyle and involved observing the differences among males and females as future elites of the Ukraine. Objective. The objective of the research is to assess the physical activity of students from the Ukraine, considering such factors as: gender, leisure time, time spent sitting, sports performed or intended to be performed, and the BMI. Materials and method. The extended ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
8
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 14 publications
5
8
0
6
Order By: Relevance
“…According to the authors, insufficient physical activity was determined in 19.2% of females and 9.9% of males. A comparison of our data with studies performed by foreign researchers revealed a similar trend -the majority of students showed a moderate and high level of physical activity, and only a small part of students was insufficiently physically active (Bergier et al, 2017;Malmborg, Bremander, Olsson, & Bergman, 2017;Niedermeier, Frühauf, Kopp-Wilfling, Rumpold, & Kopp, 2018).…”
Section: Discussionsupporting
confidence: 81%
“…According to the authors, insufficient physical activity was determined in 19.2% of females and 9.9% of males. A comparison of our data with studies performed by foreign researchers revealed a similar trend -the majority of students showed a moderate and high level of physical activity, and only a small part of students was insufficiently physically active (Bergier et al, 2017;Malmborg, Bremander, Olsson, & Bergman, 2017;Niedermeier, Frühauf, Kopp-Wilfling, Rumpold, & Kopp, 2018).…”
Section: Discussionsupporting
confidence: 81%
“…Analizuojant individualius fizinį aktyvumą lemiančius veiksnius, užsienio (El-Gilany, Badawi, El-Khawaga ir Awadalla, 2011; Năsui ir Popescu, 2014; Goje, Salmiah, Azuhairi ir Kamaruzaman, 2014;Murphy et al, 2015;Bednarek, Pomykała, Bigosińska ir Szyguła, 2016;Bergier, Bergier ir Tsos, 2017) ir Lietuvos (Stukas, Dobrovolskij ir Adomaitis, 2012;Norkus, 2012;Dobrovolskij, 2014) mokslininkų tyrimuose konstatuojama, kad studentų fiziniam aktyvumui įtakos turi lytis: vaikinai yra fiziškai aktyvesni nei merginos. Šią vyraujančią tendenciją patvirtina LEU studentų fizinio aktyvumo lygio sąsajos su lytimi: 69,5 proc.…”
Section: Tyrimo Rezultatų Aptarimasunclassified
“…Įvairių šalių studentų gyvensenos tyrimuose (Pedišić et al, 2014;Shani et al, 2014;Teixeira et al, 2016;Bergier, Bergier ir Tsos, 2017) pateikiama nemažai įrodymų, kad nepakankamas fizinis aktyvumas yra svarbi studentų sveikatos ir gyvensenos problema. J.…”
unclassified
“…En la misma línea están los trabajos de Awadalla et al 2014 . Así mismo, existen estudios comparativos entre estudiantes universitarios de EF de diferentes países, como es el caso de Haase et al (2004), Kondric et al (2013), Bergier et al (2016Bergier et al ( , 2017, y Sindik et al (2017).…”
Section: Introductionunclassified